Combination therapy for rapid treatment of severe obsessive–compulsive disorder: a case report - Lan Feng; Bin Feng; Li-yuan Luo (Journal of International Medical Research, 2019)
Objective A 29-year-old male from Guizhou, China, had been suffering from obsessive–compulsive disorder since graduation from junior high school at 14 years. He was afraid of putting glass substances in his mouth. His main symptoms were repetitive thoughts, inquiries and examinations for more than 6 hours a day. He dropped out of school and stayed at home. He had been taking 60 mg/day paroxetine for 7 consecutive years. Over the past 2 years, his obsessive–compulsive symptoms had increased and were present for 12 hours a day. Methods The patient was treated using a combination of drugs, transcutaneous electrical acupoint stimulation–exposure and response prevention therapy (TEAS–ERP) and parental involvement. Results After 28 days, his Yale–Brown Obsessive Compulsive Scale score dropped from 40 to 11 points. After 1 month, telephone follow-up showed that he was able to do housework and was ready to go to work. After 6 months, he was able to easily work, and his compulsive behaviour only occurred 1 to 2 times each day for about 0.5 minutes each time. Conclusions The combination of TEAS–ERP, sertraline and clomipramine had a rapid effect. There was no resumption of obsessive–compulsive symptoms during post-treatment follow-up.